The Effectiveness of Da’wah Through TikTok Media - Yopi Kusmiati; Musfiah Saidah; Abdul Rauf Ridzuan (Communicatus: Jurnal Ilmu komunikasi, 2026)
The rapid growth of social media has created new opportunities for Islamic da'wah activities, particularly through TikTok, a platform widely used by younger audiences. Although TikTok is primarily known as an entertainment medium, studies examining its effectiveness as a digital da'wah platform remain limited, especially those employing quantitative engagement analysis. This study aims to analyze the effectiveness of da'wah dissemination through TikTok by examining audience consumption patterns and interaction levels with da'wah content. The research adopts a quantitative approach using the Digital Action Research method. Data were collected through social media metrics analysis, including likes, comments, shares, saves, and views from da'wah content on the TikTok account @managementtabligh. The analysis was conducted descriptively and empirically, guided by Social Information Processing Theory. The findings reveal significant correlations between views and likes, as well as between comments, saves, and shares, indicating high audience engagement with da'wah content on TikTok. These results demonstrate that TikTok is an effective medium for digital da'wah due to its ability to generate active interaction and broaden the reach of religious messages. Practically, this study provides insights for da'wah practitioners in developing creative and adaptive digital strategies, while theoretically contributing to the discourse on da'wah communication in social media contexts.